Prognostic impact of the presence and management of coronary artery disease in patients undergoing TAVI. (14th October 2021) - Custodio, P; Madeira, S; Teles, R; Almeida, M; Mendes, M
Abstract: Introduction: Approximately half of transcatheter aortic valve implantaton (TAVI) candidates have coronary artery disease (CAD). Controversial results have been reported regarding the effect of the presence/severity of CAD and its management on clinical outcomes post-TAVI. Aim: To describe the presence, extension, severityand management of CAD pre-TAVIand to evaluate its impact on 2-yearmortality in areal world all comers population. Methods and population: Single centre retrospective analysis from a prospectively collected institutional registry (VCROSS) including 517 patients that underwent TAVI for severe aortic stenosis between January 2009 and December 2018. Patients who underwent pre TAVI CA in the context of ACS or at other institution were excluded n=138. Ultimately 380 entered the analysis. Obstructive CAD was defined as stenosis >50% in in major epicardial vessels (>2.5 mm). The total number of major epicardial with obstructive CAD was reported as was assessed the number of those left untreated. Univariate analysis was performed to assess 1) differences between patients with or without CAD and between those with significant CAD who have or have not undergone PCI, 2) variables associated with 2-year mortality. Binary logistic regression was performed to identify independent predictors of 2-year mortality including the presence of significant CAD and the type of management. Results: A total of 380 patients were included, 55.3% male with an average age of 83YO (±6.3), mean Euroscore II of 4.35. 76 had previous coronary artery bypassgrafting (CABG) and 136 had previous PCI (43 had both). 55 patients (14.4%) presented with normal coronary arteries, 120 (31.6%) with non-obstructive CAD and 205 (54%) with obstructive CAD. Out of the latter, 112 (29.5%) underwent PCI. Statistically significant differences were found between obstructive CAD vs non-obstructive patients in terms of age, previous history of ICP and CABG. In the subgroup population with obstructive CAD, no statistically significant differences was found in the PCI vs non PCI group, apart from previous history of ICP and CABG – Figure 1. Diabetes mellitus, previous history of percutaneous coronary intervention (PCI) and reduced ejection fraction (rEF – defined has <50% echocardiographically) had a negative prognosticimpact in the 2 year mortality of the 380 patients. 2-year mortality was 14, 5% (55 patients).The presence and management of CAD pre TAVI had no impact in 2-year mortality, when accounting for the differences in previous ICP history, CABG, age, and rEF. Conclusion: The presence and type of management of obstructive CAD in this real world all comers registry did not impact the prognosis at 2 years. Funding Acknowledgement: Type of funding sources: None.